IMPLEMENTASI STRATEGI PEMBELAJARAN INOVATIF BERBASIS MEDIA DIGITAL DI ERA PENDIDIKAN MODERN DI UNIVERSITAS PGRI WIRANEGARA - Durrotun Nafisah; Rohilatuz Zainiyah; Ayu Maya Damayanti (Jurnal Manajemen Pendidikan, 2026)
The development of digital technology demands that universities implement innovative learning strategies that are relevant to the needs of the modern education era. This study aims to describe and analyze the implementation of innovative digital media-based learning strategies at PGRI Wiranegara University. The study used a qualitative approach with a case study method. Data collection techniques included in-depth interviews with lecturers and students, observations of the learning process, and documentation studies. The results showed that the use of digital media such as learning management systems, learning videos, and interactive applications can increase student participation, learning flexibility, and material understanding. However, the implementation of these strategies still faces obstacles such as limited digital competence of some lecturers, infrastructure readiness, and variations in student learning motivation. This study concludes that innovative digital media-based learning strategies have the potential to improve learning quality if supported by strengthening lecturer capacity, adequate facilities, and sustainable institutional policies.